Long Term Progression-Free Survival in a Patient with Locally Advanced Prostate Cancer under Low Dose Intermittent Androgen Deprivation Therapy with Bicalutamide Only - Stefan Latz; Christian Fisang; Wolfram Ebert; Stefan Orth; Dirk G. Engehausen; Stefan C. Müller; Ralf Anding (Case Reports in Urology)
Androgen deprivation is a common treatment option in patients with locally advanced or metastatic prostate cancer. No case of long term treatment with an intermittent approach with only low dose bicalutamide (50 mg daily) has been described yet. We report a 60-year-old patient, initially presenting with a PSA elevation of 19.2 ng/mL in 1996. After diagnosis of well to moderately differentiated prostate cancer by transrectal biopsy, the patient underwent an open radical prostatectomy. Final diagnosis was adenocarcinoma of the prostate, classified as pT3a, pR1, pV0, and pL1. Adjuvant intermittent androgen deprivation therapy with flutamide 250 mg was applied, which was changed to bicalutamide 50 mg once daily when it became available in 2001. Six on-phases were performed and PSA values never exceeded 20 ng/mL. The patient did not experience any serious side effects. To date, there are no clinical or radiological signs of progression. Current PSA value is 3.5 ng/mL.